The effects of storytelling on primary six students' arabic vocabulary acquisition and interest - Nur Farhanah Abu Hassan (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The ancient art of storytelling has been used for decades to promote students' literacy skills and interest in learning a second language. Storytelling invites students to use their imagination and express their thoughts and feelings with utmost confidence. Research indicates that language instruction that employs storytelling fosters vocabulary acquisition among young adults and children likewise. In light of the empirical evidence supporting the use of storytelling in second language classrooms, this study examined the effectiveness of storytelling instruction in enhancing Primary Six students' Arabic vocabulary acquisition in an Islamic school, Madrasah Wak Tanjong Al-Islamiah, in Singapore. The study also explored students' perception and interest in the storytelling technique. The quasi-experimental pretest-posttest control group design was employed where two intact Primary Six classes (N = 24) were subjected to the intervention (storytelling versus Grammar Translation). The difference in vocabulary acquisition between the treatment and control groups was measured using the Vocabulary Knowledge Scale (VKS) developed by Paribahkt and Wesche (1997). A survey questionnaire (Radhwa, 2013) exploring the subjects' interest and preference in storytelling, and their perceived mastery of Arabic vocabulary was administered at the end of the last learning session. The results indicated that storytelling succeeded in enhancing students' Arabic vocabulary acquisition tremendously in the treatment group with an increase of 21.1 points from the pretest to the posttest, the effect size of which was very large at Cohen's d =3.68. However, the control group exhibited a significantly higher score in their vocabulary acquisition, surpassing the treatment group by 9.1 points in the posttest. The survey results indicate that students mostly liked storytelling as a means to learn Arabic vocabulary. However, due to the study's limitations concerning the sample size, instrument and unequal ability groups, the results should be interpreted with caution. This led the study to suggest that future research employ larger sample sizes as well as matching and random assignment procedures to ensure equal groups prior to intervention. The study also recommended that Arabic teachers be trained in the proper art of storytelling and include post storytelling activities in their Arabic classroom, such as role playing and summary writing, to further enhance students' comprehension of the stories told and their vocabulary acquisition.